Estimation of population and threats of Northern White-cheeked Gibbon (Nomascus leucogenys) in Phou Khao Khouay National Biodiversity Conservation Area, Lao PDR - Phommexay, Phansamai; Chaiyes, Aingorn; Duengkae, Prateep; Chuaynkern, Chantip; Chuaynkern, Yodchaiy (Agriculture and Natural Resources, 2024)
Importance of the work: The northern white-cheeked gibbon (Nomascus leucogenys) is classified as Critically Endangered on the IUCN red list, urgent species conservation is required. However, there remains a notable lack of information regarding gibbon population sizes, distribution and conservation efforts, particularly in regions within Lao PDR. Objectives: To estimate the population of N. leucogenys and to assess the status of threats to their existence within the Phou Khao Khouay National Biodiversity Conservation Area (PKK NBCA), Lao PDR. Materials & Methods: Listening posts were utilized to enumerate the number of gibbon groups. Density estimates were calculated by dividing the total number of groups heard in the listening area by the effective listening area. Threat identification was conducted through interviews with local people and direct observations. Subsequently, a value scale of threats was established, which was then used to rank and prioritize the identified threats. Results: The total population estimate was 23 N. leucogenys individuals within and around the PKK NBCA. These individuals were distributed among seven groups, categorized into four age classes, comprising 11 adult males, 8 adult females, 3 juveniles and 1 infant. The density of N. leucogenys was 2.33 groups/km2. Habitat loss and hunting were identified as the two primary direct threats. Main finding: The density of N. leucogenys derived from these findings was 2.33 groups/km2, with habitat loss and hunting being the two primary direct threats and posing extreme danger to the species, necessitating urgent regulatory and conservation interventions.